2022
DOI: 10.3390/bioengineering9080358
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Use of an Intraoral Scanner Affect Muscle Fatigue? A Preliminary In Vivo Study

Abstract: The purpose of this study was to evaluate muscle activation and fatigue in the operator during tooth preparation and intraoral scanning by simulating these tasks in two types of dental unit chair systems (UCS). Six participants were recruited, and the above tasks were simulated. Electrodes were placed on the skin over five types of muscles (arm, neck, and shoulder muscles), and the maximal voluntary contraction (MVC) was measured. Electromyography (EMG) was assessed during the simulation, and EMG values were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…A previous study reported that repeated use of IOSs could affect muscle fatigue 8 . This is one of the heaviest devices among medical devices used directly in the oral cavity, and the weight of IOSs ranged from 113 to 585 g 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that repeated use of IOSs could affect muscle fatigue 8 . This is one of the heaviest devices among medical devices used directly in the oral cavity, and the weight of IOSs ranged from 113 to 585 g 8 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that repeated use of IOSs could affect muscle fatigue 8 . This is one of the heaviest devices among medical devices used directly in the oral cavity, and the weight of IOSs ranged from 113 to 585 g 8 . In the present study, a survey was conducted after the experiment, and 79% of the participants preferred wired IOSs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al [ 15 ] investigated how Schroth exercises, one of the commonly used training methods for patients with adolescent idiopathic scoliosis in clinical settings, activate the paraspinal muscles in concave and convex sides; the findings provide evidence for the effectiveness of this treatment. Son et al [ 16 ] analyzed the sEMG signals of neck, shoulder, and arm muscles during dentists’ daily occupational tasks, and found that the repetition of one task causes muscle fatigue, a finding which supports the importance of rest for reducing occupation-related musculoskeletal disorders. By examining elbow flexor sEMG signals in patients after spinal cord injuries (SCIs) vs. healthy controls, Li et al [ 17 ] found that both the muscle fiber conduction velocity (indicating muscle properties) and the sEMG–force relationship (indicating central neural drive) had been altered after SCI.…”
Section: Evaluation Of Motion Patterns Using Validated Neuromuscular ...mentioning
confidence: 99%
“…Electromyography (EMG) is a method of measuring electrical signals generated in skeletal muscles to quantitatively assess muscle fatigue or exertional force ( Hou et al, 2021 ; Son et al, 2022 ). Quantitative assessment of muscle fatigue using surface electromyography (sEMG) has been the subject of numerous studies ( Zhang et al, 2019 ; Yun et al, 2020a ; Yun et al, 2020b ) leading to the need to develop electromyographic models that can correlate changes in sEMG signals with muscle fatigue ( González-Izal et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%